Physicochemical and ecotoxicological approaches for Moknine Continental Sebkha in Tunisia - Belaid, Afifa; Bekir, Karima; Beltifa, Asma; Sedrati, Mouncef; Santana Rodríguez, José Juan; Ben Mansour, Hedi (Journal of water and health, 2024)
Degradation of water quality is an emerging issue in many developing countries. In this context, industrial and domestic effluents heavily contaminate the coast of Moknine Continental Sebkha in Tunisia. The present study aimed to biomonitor the seawater quality of the Moknine Continental Sebkha coast using physicochemical and ecotoxicological approaches. The ecotoxicological assessment was performed using three species representing different trophic levels, namely Vibrio fischeri, Selenastrum capricornutum, and Lepidium sativum. In the physicochemical analysis such as BOD (biochemical oxygen demand), COD (chemical oxygen demand), TSS (total suspended solids), TOC (total organic carbon), NO3− (nitrate), AOX (adsorbable organic halogen), the recorded levels of pH and total suspended solids did not comply with the Tunisian standard (NT.09.11/1983). The ecotoxicological data confirmed that the tested water samples displayed toxicity to two test indicators L. sativum and S. capricornutum. A targeted chemical screening of the Moknine Continental Sebkha coast previously performed revealed the presence of total mercury, four phthalate acid esters, and one non-phthalate plasticizer, a fact that could explain the observed ecotoxicological effects and therefore might harm the biotic area and the health of the surrounding population.